Sanctuaries, oracles, mountains and sacred order in the Vilcabamba-Cusco mountain range - Bolívar Yapura, Wilber (2021)
This work is built on the basis of archaeological explorations in the Vilcabamba mountain range, depository of a vast amount of archaeological remains, which correspond to various periods and phases of human occupation, our objective was the sacred mountains in their role as deities, protective guardians and oracles; In collaboration with Andean priests, we were able to perceive that they have a sacred and hierarchical order, they are a brotherhood with a territory, they talk making decisions for the climate of the region. His subjects ask permission with offerings to travel through their territory, carry out their activities, as well as be protected. The qualities that the area possesses are framed in its geographical characteristics with peculiar architecture, adapted to the sacred geography, associated with a territorial management of volumes and solutions to the difficult topography, in addition to the conduction of spaces within the conception of the landscape in the Inka ideology.